New challenges for the European energy security. The new energy routes from South to North - Sakoufakis, Georgios (Πανεπιστήμιο Πελοποννήσου, 2023)
This paper refers to the new EU energy planning that is being pursued with the aim of energy transition towards climate neutrality, decoupling from Russian energy and achieving energy security. It focuses mainly on the new South-North energy routes that are being shaped to achieve these objectives, focusing on South-Eastern Europe and the Eastern Mediterranean. The chapters describe the institutional framework and the new policies and instruments that the EU has put in place for this purpose. The pipelines that transport gas from South to North and contribute to the decoupling from Russian gas are examined, and the LNG infrastructure system in the Mediterranean is presented. It also describes the interconnections and power cables that will carry electricity from the Mediterranean south to central Europe, and the emerging infrastructure landscape for the production and transport of hydrogen, which is seen as the key fuel of the future for industry and transport in the EU. The conclusions underline the importance of the new planning and the future critical role of the regions of South-Eastern Europe, Eastern Mediterranean and North Africa for Europe's energy sufficiency and security.
Νέες προκλήσεις για την ευρωπαϊκή ενεργειακή ασφάλεια. Οι νέες ενεργειακές οδεύσεις από τον Νότο στον Βορρά
Keywords: Energy; Natural gas; Energy policy; Energy; Energy transition; Energy security; EU energy policy; Natural gas; Electrical interconnections; South-Eastern Europe; Eastern Mediterranean; North Africa